Sequentially immune‐induced antibodies could cross‐neutralize SARS‐CoV‐2 variants. Issue 1 (25th February 2022) - Lv, Qi; Zhou, Shasha; Qi, Feifei; Zhang, Yaqing; Li, Fengdi; Liu, Mingya; Bao, Linlin
Abstract: Background: The Omicron (B.1.1.529) SARS‐COV‐2 variant has raised serious concerns because of its unprecedented rapid rate of spreading and the fact that there are 36 mutations in the spike protein. Since the vaccine‐induced neutralizing antibody targets are the spike protein, this may lead to the possibility of vaccine‐induced humoral immunity escape. Methods: We measured the neutralizing activity in vitro for Omicron and compared this with wild type (WH‐09) and Delta variants in human and monkey sera from different types of immunity. The monkey sera samples were collected at 1 and 3 months post three‐dose inactivated (PiCoVacc) and recombinant protein (ZF2001) vaccination. Human sera were collected from 1 month post three‐dose inactivated vaccination. Results: In inactivated vaccine sera, at 1/3 months post three‐dose, geometric mean titers (GMTs) of neutralization antibody (NAb) against the Omicron variant were 4.9/5.2‐fold lower than those of the wild type. In recombinant protein vaccine sera, GMTs of NAb against Omicron were 15.7/8.9‐fold lower than those of the wild type. In human sera, at 1 month post three‐dose inactivated vaccination, GMTs of NAb against Omicron were 3.1‐fold lower than those of the wild type. Conclusion: This study demonstrated that despite a reduction in neutralization titers, cross‐neutralizing activity against Omicron and Delta variants was still observed after three doses of inactivated and recombinant protein vaccination. Abstract : Given the Omicron variant potential to escape vaccine‐induced humoral immunity, we measured the cross‐neutralizing activity for variants in sera were collected at different months post three‐dose vaccination. The neutralization antibody titers of Omicron were 3.1–15.7 fold lower than those of the wild type in different immune serum. Despite a reduction in neutralization titers, it still possessed cross‐neutralizing activity against Omicron and Delta variants after three doses of inactivated and recombinant protein vaccination.